Species limits in the Rhodocoma gigantea (Kunth) Linder complex - Mafa, Paseka (Department of Biological Sciences, 2017)
Rhodocoma gigantea and Rhodocoma foliosus have been recognised by earlier authors as separate species on the basis of perianth length and shape. Linder (1985) superficially lumped these two species under Rhodocoma gigantea arguing that the difference between the two appear to be brought by ecological gradient. Numerical phenetic analyses of 19 quantitative floral morphological characters investigated from 33 herbarium specimens reveal that Rhodocoma gigantea complex consists of two groups. One group corresponded to Rhodocoma gigantea, having longer and wider spikelets, perianth segments and bracts, while the other correspond to Rhodocoma foliosus having shorter and thinner female spikelets, bracts and perianth segments than the former. Minimum spanning tree also reveal the two groups are geographically isolated. The former group occur in the western part of the south coast along the Langeberg in Swellendam and Riversdale districts and the latter is widely distributed on the Outeniekwaberg, Tsitsikama mountains to Zuurberg with outliers reaching as far as Uitenhage. The Gouritz river appears to be the geographical barrier between these two species. The species boundaries of this complex are discussed and the two groups are suggested to be separated based on the phenetic species concepts.